PENGARUH WEBSITE QUALITY ,KEPERCAYAAN WEBSITE PADA PERSEPSI DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN - Joko Samboro (Politeknik Negeri Malang, 2018)
The main objectives of this research is: To find out and analyze the influence of website quality, trust in customer loyalty through customer perception. The research location was in Malang State Polytechnic, while the population of this study were all customers who had been online more than once, while the sample consisted of 70 customers who were selected according to the research objectives. The results showed that the data used was valid and reliable, the better the Web Quality and the level of trust the stronger the Customer Perception and the better the Customer Perception, the higher the Loyalty.The effect of the total variables studied was 14.16%.